2019
DOI: 10.1016/j.amsu.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The evidence-base for the management of flexor tendon injuries of the hand: Review

Abstract: HighlightsThere is no consensus on the optimal flexor tendon repair technique at each anatomical flexor zone.There is paucity of high quality evidence.Heterogenous study designs limit inter-study comparisons.Patient reported outcome measures are crucial but there is a perennial need for robust disease-specific tools to be utilised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…The technique used for the control group, 4-core strand suture with a peripheral suture, has been debated to be the gold standard that allow optimal balance between repair strength, time of procedure, and also allows for quick rehabilitation [3,5,7,17]. With the traditional repair, rupture occurred at the knot level, compatible with prior evidence [3,6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The technique used for the control group, 4-core strand suture with a peripheral suture, has been debated to be the gold standard that allow optimal balance between repair strength, time of procedure, and also allows for quick rehabilitation [3,5,7,17]. With the traditional repair, rupture occurred at the knot level, compatible with prior evidence [3,6].…”
Section: Discussionmentioning
confidence: 98%
“…Flexor tendon injuries of the hand, especially in zone 2, account for less than 1% of all hand injuries, but are di cult to treat and are associated with poor outcome [1]. While major progress has been made with the treatment of these injuries, current surgical treatment relies mostly on conventional suturing techniques with dissatisfactory results, concluding in re-operation rates of 6%-17%, and complication rate of up to 20% [1][2][3][4][5]. Furthermore, a considerable wide diversity in suturing techniques used by different health providers, might imply a superior technique has yet to be discovered [1,4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…tendon grafts, tendon transfers, end-to-end repair and arthrodesis of interphalangeal joints, however, by any means a worse outcome has been reported compared to the usual flexor tendon injuries [ 5 ]. Flexor tendon ruptures after VLP fixation could be categorized in zone V tendon injuries, and there are few reports on the outcome of the zone V tendon repair [ 10 ]. Rubensson et al reported that the results of ROM after reconstruction with free tendon graft are as good enough as the previous reports about flexor tendon reconstructions [ 5 ], but the decision regarding which of the various techniques should be applied is possibly dependent on the condition of ruptured tendon stumps.…”
Section: Discussionmentioning
confidence: 99%
“…Advancement in surgical repair techniques and materials have enabled early active motion following flexor tendon repair, yet there is a lack of high-quality evidence to inform best practice for post-operative rehabilitation. [2][3][4][5] Existing systematic reviews exploring flexor tendon rehabilitation have assessed different approaches to splinting, for example including or excluding the wrist, 5 or different exercise programmes, for example passive or active mobilisation. 3,4,6 However, none of these reviews were able to draw firm conclusions.…”
Section: Introductionmentioning
confidence: 99%